Overweight and obesity: A review of their relationship to metabolic syndrome, cardiovascular disease, and cancer in South America - Aballay, Laura Rosana (2013)
Socioeconomic and demographic transformations are occurring very rapidly in some areas of the world, especially in South America, and are accompanied by changes in lifestyle, dietary patterns, and the epidemiological profile of prevalent diseases. This review examines whether obesity and overweight are related to metabolic syndrome, cardiovascular disease, and cancer in South America. Research carried out in more than 6,000 cases and controls was evaluated, along with most of the available publications related to South America. In South America, obesity and risk factors for cardiovascular disease are related mainly to aging, ethnicity effects, and preventable risky lifestyle conditions. Most of the studies that found an association between cancer and obesity are from the Southern Cone, the geographic area most affected by this pathology. Overall, the prevalence of metabolic syndrome was highest in Chile, followed in decreasing order by Colombia, Peru, Argentina, and Ecuador, with differences noted between urban and rural areas or between urban and periurban areas. Obesity and cancer may be preventable, at least in part, by healthy behavior; hence, exercise, weight control, and healthy dietary habits are important to reduce the risk of these major chronic diseases.